2003
DOI: 10.1002/asi.10281
|View full text |Cite
|
Sign up to set email alerts
|

Do nondomain experts enlist the strategies of domain experts?

Abstract: User studies demonstrate that nondomain experts do not use the same information-seeking strategies as domain experts. Because of the transformation of integrated library systems into Information Gateways in the late 1990s, both nondomain experts and domain experts have had available to them the wide range of information-seeking strategies in a single system. This article describes the results of a study to answer three research questions: (1) do nondomain experts enlist the strategies of domain experts? (2) if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 31 publications
2
35
0
2
Order By: Relevance
“…Framework research confirmed other findings relating to undergraduate preference for easy and convenient methods of information searching, and their propensity to use simple search strategies, and search engines (Becker, 2003;Dalgleish & Hall, 2000;Drabenstott, 2003;Given, 2002;Liu & Yang, 2004;Valentine, 1993). Specifically, the Framework research noted the growth in the dominance of Google over the 5 years of the study.…”
Section: Student Searching Strategiessupporting
confidence: 77%
“…Framework research confirmed other findings relating to undergraduate preference for easy and convenient methods of information searching, and their propensity to use simple search strategies, and search engines (Becker, 2003;Dalgleish & Hall, 2000;Drabenstott, 2003;Given, 2002;Liu & Yang, 2004;Valentine, 1993). Specifically, the Framework research noted the growth in the dominance of Google over the 5 years of the study.…”
Section: Student Searching Strategiessupporting
confidence: 77%
“…All four schemes essentially bring like items together in different ways, but the Associative Index also creates a cognitive vehicle for the user to put together his/her thinking, thus creating the prior conditions necessary for information need identification and successful information searching to occur (cf. also, Ellis, 1989;Drabenstott, 2003).…”
Section: The Information Need Identification Systemmentioning
confidence: 95%
“…Several small-scale interview and focus-group-based studies examined how students perceive their information behavior and search strategies (Becker, 2003;Drabenstott, 2003;Valentine, 1993;Wildemuth, 2004). If information seeking and learning are intertwined, then some of these studies produce puzzling findings, with little evidence of learning about information seeking.…”
Section: Student Information-behavior Researchmentioning
confidence: 98%